Relationship between ocular abnormalities and hematologic alterations in patients infected naturally by ehrlichia canis - Piso, Dunia Yisela Trujillo; Barreto, Monica Yamile Padilla; Bonilla, Maria Del Pilar Sánchez; de Andrade, Alexandre Lima [UNESP] (FapUNIFESP (SciELO), 2021)
To determine the association between ocular abnormalities and hematologic findings in Ehrlichia canis-infected dogs, 120 dogs suspected of canine ehrlichiosis were studied. All patients were subjected to rapid serologic diagnostic test for Ehrlichia canis, and the diagnosis was confirmed by quantitative PCR. PCR-positive patients underwent ophthalmologic examination and a hemogram and were grouped into patients with thrombocytopenia and anemia (G1), patients with thrombocytopenia (G2), and patients without hematologic disorders (G3). For ophthalmic evaluation, the patients were grouped into those having mild, severe, both mild and severe, and no ocular alterations. All patients presented with uveitis (100%). Severe ocular disorders predominated in G1 and G2 patients. Dogs with anemia and leukopenia showed severe ocular disorders. In dogs with a greater number of leukocytes and copies/µl of the TRAG gene, the intraocular pressure (IOP) tends to decrease and vice versa (r = −0.23, r = −0.26). In conclusion, uveitis is the earliest ocular alteration of canine ehrlichiosis. The severity of ocular abnormalities in patients with ehrlichiosis is associated with thrombocytopenia and may be aggravated by anemia and leukopenia. The hemogram and IOP are useful tools for predicting eye involvement in Ehrlichia canis-infected patients. In regions where Ehrlichia canis is endemic, the use of the tonometer should be routinely in dog general consultation.
Alterações hematológicas e sua relação com anormalidades oculares em pacientes infectados naturalmente com ehrlichia canis
Keywords: Ehrlichia; Hematology; IOP; Thrombocytopenia; TRAG gene; Uveitis